Globalizing the Certification of Systems Engineers. Issue 3 (12th November 2019) - Wright, Courtney
ABSTRACT: What defines an international airport? Flights to and from other countries? Big runways and high volume of passengers? US definitions of international airports focus on the facility's ability to process passengers entering from another country. They do not look at whether aircraft can or do enter that port, just whether their passengers are allowed to leave the airport if it is their first port of entry in the US. It is about what can, theoretically, be done with people from other countries, rather than how well people around the globe are actually interacting. How do we define an international professional society or its international certification program? We might start by looking at the three factors listed above: May people from more than one country participate? Can people from more than one country participate? And, do people from more than one country participate? This "more than one country" bar is pretty easy to meet, thanks to the UK, so let's move to all countries. This is a much greater challenge and the logic behind referring to INCOSE as a global certification program rather than the easier international. In our context, international means including some other countries, often those with similar cultures or technologies, where global is both broader and deeper, and for us, this includes modifying our baseline certification practices in response to feedback from other cultures.